(untitled) (Texas Journal of Medical Science, 2023)
Orthodontics for children is a specialized branch of dentistry that focuses on the treatment of dental and jaw abnormalities in young patients. It is essential to address dental issues early in life to ensure proper jaw growth and tooth alignment. By using braces, retainers, and other devices, orthodontists can guide the development of a child’s teeth and jaws, ensuring a healthy and functional smile for years to come